‘One Stop’ Therapy has a Satisfying Performance on AF Patients with Interatrial Communication: Evidence from Pooled Clinical Experience - Zhi-Yuan Zhang; Feng Li; Chi Geng; Yu-Qi Chen; Si-Liang Peng; Yao-Ting Zhang; You Zhang; Xiao-Song Gu; Hui Li (Reviews in Cardiovascular Medicine)
Background: Left atrial appendage closure (LAAC) has been reported to be a viable alternative to prevent thromboembolic events for atrial fibrillation (AF) patients. Interatrial communication closure, such as atrial septal defect (ASD) and patent foramen ovale (PFO) closure could significantly decrease the occurrence of stroke. For AF patients with interatrial communication, the success rate as well as the long-term outcomes of ‘One stop’ closure remain elusive. Methods: Studies were systematically screened using online databases (including PubMed, Cochrane Library, Web of Science, Embase, China National Knowledge Infrastructure (CNKI) database, and WanFang database) from their establishment to 1st August 2024. We utilized a fixed-effect model to synthesize the success rate and the long-term outcomes. Subgroup analysis was performed to identify the potential confounders. Results: A total of 7 studies comprising 156 patients were included. ASD/PFO closure combined with LAAC showed a high degree of feasibility, with a success rate of 1.00 (95% CI: 0.99, 1.00; p < 0.001). Meanwhile, ‘One stop’ ASD/PFO closure combined with LAAC exhibited a high long-term safety and a low occurrence of complications. Moreover, subgroup analysis revealed that the bleeding event occurrence was relatively higher in the male proportion ≥50% subgroup and HAS-BLED score ≥3 subgroup, respectively. Conclusions: ASD/PFO closure combined with LAAC has a satisfying performance on AF patients with interatrial communication. The PROSPERO Registration: CRD42023462221, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023462221.